Beschreibung der zuletzt von der Bayerischen Staatsbibliothek, München erworbenen äthiopischen Handschriften - Six, Veronika (Aethiopica, 2018)
A description of the collection of Ethiopian manuscripts in the Bayerische Staatsbibliothek, Munich, can be found in the volumes of the Union Catalogue of Oriental Manuscripts in Germany (Verzeichnis der orientalischen Handschriften in Deutschland, VOHD). However, by 2016, the library’s holdings had been augmented by a further twenty Ethiopian manuscripts: some were donations, but most had been purchased at auctions. They are presented in this article according to the rules of the VOHD. Of the four Psalters, Cod. aethiop. 179, probably dating from the sixteenth century based on paleographic criteria, should be highlighted. Furthermore there are seven parchment scrolls and two leporello manuscripts. Also worth mentioning is a Senkessār for the second part of the year, as well as a Deggwā and several other manuscripts, all with illustrations that have been added at a later date to the original text but which have a characteristic style or use wellknown motifs. Cod. aethiop. 173 is also interesting since there are not many other such manuscripts, though at first sight the title ʿEnzira sebḥat simply suggests a common hymn.